2023
DOI: 10.1002/hsr2.1525
|View full text |Cite
|
Sign up to set email alerts
|

Personality, dietary identity, mental and sleep health in vegans and vegetarians: A preliminary cross‐sectional study

Christle Coxon,
Piril Hepsomali,
Karen Brandt
et al.

Abstract: Background and AimsPlant‐based diets have gained popularity over the past decade. However, research regarding mental and sleep health benefits of following plant‐based diets are conflicting. As there are associations between mental/sleep health and various personality traits, and personality may differ between individuals who follow different diets, in this preliminary study, we examined the associations between mental and sleep health and (i) personality and (ii) dietary identity in individuals who follow veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…However, more studies found an increased risk of depression in vegetarians [41][42][43][44]8], whereas others found no association [45][46][47], or that a vegetarian diet may be beneficial for depression [48]. Evidence regarding the association of vegetarians and diet with depression is conflicting [49]. The study found that vegetarian men exhibited a higher prevalence of depressive symptoms and nutritional deficiencies in iron or cobalamin, which may be a contributing factor.…”
Section: Association Between Vegetarian Diet and Depressionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, more studies found an increased risk of depression in vegetarians [41][42][43][44]8], whereas others found no association [45][46][47], or that a vegetarian diet may be beneficial for depression [48]. Evidence regarding the association of vegetarians and diet with depression is conflicting [49]. The study found that vegetarian men exhibited a higher prevalence of depressive symptoms and nutritional deficiencies in iron or cobalamin, which may be a contributing factor.…”
Section: Association Between Vegetarian Diet and Depressionmentioning
confidence: 89%
“…However, the exclusion of any food group has been associated with an increased risk of depression. This suggests that there may be an association between depression and the exclusion of any food group, Inventory (BFI); Empathy Quotient 10 (EQ-10); DASS; Warwick-Edinburgh Mental Well-being Scales (WEMWBS); Pittsburgh Sleep Quality Index (PSQI); Dietarian Identity Questionnaire (DIQ); EPIC Food Frequency Questionnaire (FFQ) These preliminary findings suggest that not only personality traits, but also plant-based diets have been associated with better mental health Coxon et al, 2023[49]…”
mentioning
confidence: 99%